Gambaran Kelelahan Pada Anak Penderita Kanker Yang Menjalani Kemoterapi - syalaisha Faatihah; Agnita Utami; Rani Lisa Indra (Jurnal Ilmiah Keperawatan STIKES Hang Tuah Surabaya, 2026)
Introduction: Cancer is a major cause of morbidity and mortality in children worldwide. Chemotherapy is commonly employed as a primary treatment modality in pediatric oncology; however, fatigue is frequently reported as one of its most prominent adverse effects. Objectives: This study aimed to describe the dimensions of fatigue among pediatric cancer patients undergoing chemotherapy. Methods: This descriptive quantitative study used consecutive sampling. A total of 40 pediatric cancer patients undergoing chemotherapy at the Seruni Integrated Cancer Unit of Arifin Achmad General Hospital, Riau Province, were recruited as respondents. Fatigue levels were measured using the Pediatric Quality of Life Inventory (PedsQL) Multidimensional Fatigue Scale and analyzed descriptively. Results: The majority of respondents were aged 5–7 years (35%), male (52.5%), and diagnosed with leukemia (82.5%). The mean total fatigue score was 64.85 (0–100), consisting of General Fatigue (63.58), Sleep/Rest Fatigue (54.65), and Cognitive Fatigue (76.35). Lower scores indicated greater fatigue severity, with the Sleep/Rest dimension representing the most affected domain Conclusions: Pediatric cancer patients undergoing chemotherapy experience varying levels of fatigue across multiple dimensions. These findings highlight the importance of addressing physiological and psychological fatigue-related symptoms to support children’s adaptation during chemotherapy